DETEKSI KANDUNGAN RHODAMIN B PADA SAUS SERTA CEMARAN BORAKS DAN BAKTERI SALMONELLA SP. PADACILOK KELILING SALATIGA - Ardhikajaya Wahyu Prasetya; Lusiawati Dewi (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2016)
ABSTRACTBorax and rhodamine B are preservative and dye banned to be used in food products. However, some traders still use borax and rhodamine B to their food and drink products. Cilok is a kind of food liked by schoolchildren and categorized as street vendor food (PKL). Most of food sold by street vendor has not touched by strict control from BPOM, so its quality is not good. Pentol cilok is a food made by starch. It tastes delicious and chewy. Furthermore, it is liked by schoolchildren. Cilok is also served by adding the sauce in order to make it tastier. It is common to add dye in that sauce and the dye is not natural dye nor food coloring. In the cilok, the contamination of microbe especially Salmonella sp. is influenced by unhygienic process. This research aims to find out borax and Salmonella sp. contamination and also the existence of rhodamine B on the cilok sauce. The methods used in this research are qualitative, quantitative, and the detection of Salmonella sp. contamination. The result shows, of the 8 tested samples, 4 samples (sample B, C, E, and H) contain little amount of borax, the sauce contains no rhodamine B. This can be seen from Rf value and color reaction test. On the testing of Salmonella sp., there are bacteria before boiling process (when cilok is still in the form of dough) and there are no bacteria after boiling and steaming process, so it is safe to be consumed.